2018
DOI: 10.1083/jcb.201708153
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged cyclin-dependent kinase inhibition results in septin perturbations during return to growth and mitosis

Abstract: We investigated how coordinate polarization, budding, and anaphase during a unique developmental program called return to growth (RTG) in which cells in meiosis return to mitosis upon nutrient shift. Cells reentering mitosis from prophase I deviate from the normal cell cycle by budding in G2 instead of G1. We found that cells do not maintain the bipolar budding pattern, a characteristic of diploid cells. Furthermore, strict temporal regulation of M-phase cyclin-dependent kinase (CDK; M-CDK) is important for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…Consistent with this, we observed that gin4-AID hsl1-AID caused a failure in cell separation in nearly all cells at the end of the first cell cycle following the addition of auxin (Video 2). Previous studies also found that gin4∆ and hsl1∆ cause defects in spindle positioning (Fraschini et al 2006;Grava et al 2006;Gihana et al 2018). We observed only a few defects in spindle positioning during the first cell division after addition of auxin to gin4-AID hsl1-AID cells.…”
Section: Gin4-related Kinases Are Required For Normal Control Of Bud Growth During Mitosissupporting
confidence: 68%
See 1 more Smart Citation
“…Consistent with this, we observed that gin4-AID hsl1-AID caused a failure in cell separation in nearly all cells at the end of the first cell cycle following the addition of auxin (Video 2). Previous studies also found that gin4∆ and hsl1∆ cause defects in spindle positioning (Fraschini et al 2006;Grava et al 2006;Gihana et al 2018). We observed only a few defects in spindle positioning during the first cell division after addition of auxin to gin4-AID hsl1-AID cells.…”
Section: Gin4-related Kinases Are Required For Normal Control Of Bud Growth During Mitosissupporting
confidence: 68%
“…However, an alternative model is that aberrant growth caused by loss of Gin4-related kinases is an indirect consequence of mitotic delays. For example, there is evidence that loss of Gin4-related kinases causes defects in positioning the mitotic spindle, which could cause chromosome segregation defects and associated mitotic delays that lead to abnormally prolonged growth (Fraschini et al 2006;Grava et al 2006;Gihana et al 2018). In this case, growth defects would be a secondary consequence of mitotic spindle defects.…”
Section: Introductionmentioning
confidence: 99%
“…Successful completion of meiosis requires that cells remain committed to completing meiosis, even in the presence of a mitosis-inducing signal. Historically, meiotic commitment has been studied in budding yeast due to the ease of providing meiotic cells a mitosis-inducing signal, nutrient-rich medium (Ballew & Lacefield, 2019a, 2019b; Esposito & Esposito, 1974; Gihana, Musser, Thompson, & Lacefield, 2018; Honigberg & Esposito, 1994; Nachman, Regev, & Ramanathan, 2007; Sherman & Roman, 1963; Simchen, 2009; Simchen et al, 1972; Tsuchiya et al, 2014). However, only a few genes have been implicated in meiotic commitment (Ballew & Lacefield, 2019a; Esposito & Esposito, 1974; Honigberg, Conicella, & Espositio, 1992; Honigberg & Esposito, 1994; Tsuchiya et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to initiating the protocol, the features of the starting strain for the screen should be carefully considered. To study genes involved in progression through meiosis, meiotic commitment, and return-to-growth, we typically use cells that express three fluorescently-tagged proteins to monitor different stages of meiosis: Zip1-GFP, which marks the synaptonemal complex in prophase I, Spc42-mCherry, a component of spindle pole bodies, and GFP-Tub1, to monitor the spindle morphology at the different stages of meiosis ( Carminati and Stearns, 1997 ; Donaldson and Kilmartin, 1996 ; Gihana et al., 2018 ; Scherthan et al., 2007 ; Tsuchiya et al., 2011 ; Tsuchiya and Lacefield, 2013 ). Although both Zip1 and Tub1 are tagged with GFP, we can easily distinguish between the markers due to differences in temporal regulation and morphology.…”
Section: Before You Beginmentioning
confidence: 99%